Pengaruh Model Project-Based Learning Terhadap Keterampilan Investigasi dan Hasil Belajar IPA Siswa SMP Negeri 4 Mazo - Hardikupatu Gulo; Dasari Waruwu (Program Studi Pendidikan Biologi - Universitas Nias, 2025)
The low investigative skills and science learning outcomes of junior high school students are major obstacles to the development of scientific literacy. This study aims to examine the effect of Project-Based Learning on investigative skills and science learning outcomes. The study was conducted at SMP Negeri 4 Mazo in the odd semester of the 2024/2025 academic year using a quasi-experimental design with two groups: an experimental class learning with Project-Based Learning and a control class learning with direct learning. Data on investigative skills were collected through performance tests and standardized observation rubrics, while cognitive learning outcomes were measured with a validated multiple-choice test. Data were analyzed using an independent sample t-test after all prerequisites were met. The results showed a significant difference, with the Project-Based Learning group achieving an average investigative skills score of 78.5 and a learning outcome of 82.3, convincingly surpassing the control group. These findings confirm that Project-Based Learning is able to encourage students to design investigations, collect evidence, and draw conclusions independently, while strengthening conceptual mastery. A significant implication of this study is the availability of empirical evidence for science teachers to adopt this model to develop 21st-century inquiry skills.